2023
DOI: 10.3390/ijms24065104
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of Antibody Responses of Gam-COVID-Vac-Vaccinated Subjects Suggests Involvement of Epitopes Outside RBD in SARS-CoV-2 Neutralization

Abstract: Millions of people have been vaccinated with Gam-COVID-Vac but fine specificities of induced antibodies have not been fully studied. Plasma from 12 naïve and 10 coronavirus disease 2019 (COVID-19) convalescent subjects was obtained before and after two immunizations with Gam-COVID-Vac. Antibody reactivity in the plasma samples (n = 44) was studied on a panel of micro-arrayed recombinant folded and unfolded severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) proteins and 46 peptides spanning the spike … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Thus MIAs can only measure whether antibodies can prevent the interaction of RBD and ACE2. In this context, it must be mentioned that epitopes located outside RBD in the S protein may also play a role in virus-neutralization [ 45 , 46 , 47 , 48 , 49 , 53 , 126 , 127 ]. It is thus possible that certain subjects lacking antibodies blocking the RBD–ACE2 interaction may still contain NAbs.…”
Section: Molecular Interaction Assays Miasmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus MIAs can only measure whether antibodies can prevent the interaction of RBD and ACE2. In this context, it must be mentioned that epitopes located outside RBD in the S protein may also play a role in virus-neutralization [ 45 , 46 , 47 , 48 , 49 , 53 , 126 , 127 ]. It is thus possible that certain subjects lacking antibodies blocking the RBD–ACE2 interaction may still contain NAbs.…”
Section: Molecular Interaction Assays Miasmentioning
confidence: 99%
“…Regarding mice, it is important to create mouse strains expressing human ACE2 to render mice susceptible for infection. The animal models show variability regarding susceptibility to different virus strains, severity of infection, symptoms and pulmonary pathology [ 127 , 128 , 129 , 130 , 131 , 132 ]. Currently the Syrian hamster model is one of the most frequently used animal models for SARS-CoV-2 infections [ 128 , 129 ].…”
Section: In Vivo Modelsmentioning
confidence: 99%
“…A recent plaque reduction neutralization assay revealed that the neutralization activity against S1 is almost twice as high as against RBD, suggesting the presence of additional neutralizing antibodies that do not target RBD itself . Another study reported the plasma’s inability to inhibit the ACE2–RBD interaction while simultaneously showing virus neutralization activity in a pseudovirus neutralization assay . A comparative analysis of a neutralization assay with fully replicative SARS-CoV-2 and a pseudovirus with S protein on the virus’s surface demonstrated that the neutralization activity mainly depends on the S protein .…”
mentioning
confidence: 99%
“… 23 Another study reported the plasma’s inability to inhibit the ACE2–RBD interaction while simultaneously showing virus neutralization activity in a pseudovirus neutralization assay. 24 A comparative analysis of a neutralization assay with fully replicative SARS-CoV-2 and a pseudovirus with S protein on the virus’s surface demonstrated that the neutralization activity mainly depends on the S protein. 25 Consequently, trimeric S proteins in surrogate neutralization assays may provide more accurate neutralization levels than in currently utilized systems.…”
mentioning
confidence: 99%